An Update on Hypersensitivity Pneumonitis - Gulati, Mridu (Current Respiratory Medicine Reviews, 2016)
Hypersensitivity pneumonitis is a form of interstitial lung disease caused by a wide array of respirable particles. Given the widespread prevalence of many implicated exposures, contributing factors such as genetic predisposition and concomitant environmental factors likely influence the risk of disease development. Common causes include a range of bacterial and fungal species, and a number of chemical exposures such as to isocyanates. Exposures to microbial contaminants can occur in a range of domestic, recreational and occupational settings. Occupational exposures to microbial contamination include and are not limited to the farming industry, the manufacturing industry which frequently requires the use of metalworking fluids, and the food industry. Diagnostic assessment initially relies on a high index of clinical suspicion. Subsequent workup integrates clinical history, pulmonary function testing and radiologic imaging with a high resolution chest CT scan. In certain clinical scenarios, serological testing, bronchoscopy with bronchoalveolar lavage and/or surgical lung biopsy may be informative.
Keywords: hot tub lung